The materiality of cyberthreats: securitization logics in popular visual culture. Issue 2 (4th May 2019) - Dunn Cavelty, Myriam
ABSTRACT: Critical security studies literature has only recently begun to take into account the influence of material aspects in the field of cybersecurity. This article traces securitization logics in popular visual culture to show how these representations make sense of technical incidents politically via material objects. Using a mix of discourse analysis and semiology, three types of threat representations are identified, showing a shift from depicting computers themselves as the main threat to the manipulation of data as exercise of power and finally, the wielding of code as weapon to create physical damage. Material objects define the space of engagement, being both the threat and what is threatened. By destabilising old authority structures, they pose questions about legitimate political alternatives in a world where only a handful of technical geniuses have the power to shape rules and take on the role of 'the protector'.